Akibat Hukum Pembagian Warisan terhadap Anak Perempuan Menurut Hukum Adat Batak Toba dan Hukum Islam - Daniel R. Sihite; Desriani Ronay Fiona Purba; Bayu Adrian; Zoan Gaharu Parangin-Angin; Boy Dippu Tua Simbolon; Stefy Margaretha; Parlaungan Gabriel Siahaan; Sri Hadiningrum (Journal on Education, 2024)
The mini research assignment for group 4 from class E PPKn 2022 is entitled: "The Legal Effects of Distribution of Inheritance on Girls According to Toba Batak Customary Law and Islamic Law". This mini-research examines the distribution of inheritance to daughters according to Toba Batak customary law and Islamic law. The aim of this research is to find out how inheritance is distributed to daughters according to Toba Batak customary law and Islamic law. This mini-research uses Qualitative Research Methods with the type of Normative Legal (Empirical) research. Data collection techniques through interviews, documentation, and data sources taken from the community. If we look at the distribution of inheritance from Toba Batak customary law, it is true that it is more profitable for sons, it is true that daughters also get inheritances, but not as much as inheritances given to sons. This happens because men are the successors of the clan and will carry out greater duties and responsibilities in the family. Meanwhile, women will later become someone else's property and inherit from their husbands. Meanwhile, according to Islamic law, in terms of dividing inheritance, women also receive an inheritance, but not as much as the inheritance given to men.